Apricots from Chernobyl : narratives - Novaković, Josip; Novakovich, Josip (Saint Paul : Graywolf Press, 1995)
Apricots from Chernobyl is a collection of beautifully crafted narratives on life in the former Yugoslavia, and subsequently in America, by widely published author and essayist Josip Novakovich. Exploring topics that include emigration, definition of borders, societal diversity, and the decay of religion, Novakovich's narratives are approachable and engaging. Whether describing his feelings of apprehension upon approaching a boarder, or the difficulties encountered when writing in a second "tongue," Novakovich is fresh, wry, and consistently entertaining. Apricots from Chernobyl offers a candid portrayal of global existence, skillfully blending its sometimes brutal but often ironic and humorous realities.